A Survey of Digital Rectal Examination Training in Canadian Medical Schools - Alysha Nensi; Nilesh Chande (Canadian Journal of Gastroenterology)
BACKGROUND: The digital rectal examination (DRE) is important for the diagnosis of a variety of gastrointestinal, urological and gynecological disorders. However, it appears that Canadian medical students may not be adequately taught nor provided the opportunity to practice their skills often enough. The present study was an analysis of the current practices in DRE teaching and evaluation in undergraduate medicine programs across Canada.